High-energy diffraction of particles and nuclei - Jenkovszky, László; Nagy, István (Вопросы атомной науки и техники, 2012)
After a brief historical overview, we present recent results on high-energy diffraction, elastic and inelastic, with emphasis and comments on the recent experimental results from the Large Hadron Collider (LHC) at CERN.